A Narrative Overview of Coronavirus Infection: Clinical Signs and Symptoms, Viral Entry and Replication, Treatment Modalities, and Management - Chavda, Vishal; Yadav, Dhananjay; Parmar, Harisinh; Brahmbhatt, Raxit; Patel, Bipin; Madhwani, Kajal; Jain, Meenu; Song, Minseok; Patel, Snehal (Current Topics in Medicinal Chemistry, 2024)
The global pandemic known as coronavirus disease (COVID-19) is causing morbidity and mortality on a daily basis. The severe acute respiratory syndrome coronavirus-2 (SARS-CoV- -2) virus has been around since December 2019 and has infected a high number of patients due to its idiopathic pathophysiology and rapid transmission. COVID-19 is now deemed a newly identified “syndrome” condition since it causes a variety of unpleasant symptoms and systemic side effects following the pandemic. Simultaneously, it always becomes potentially hazardous when new variants develop during evolution. Its random viral etiology prevents accurate and suitable therapy. Despite the fact that multiple preclinical and research studies have been conducted to combat this lethal virus, and various therapeutic targets have been identified, the precise course of therapy remains uncertain. However, just a few drugs have shown efficacy in treating this viral infection in its early stages. Currently, several medicines and vaccinations have been licensed following clinical trial research, and many countries are competing to find the most potent and effective immunizations against this highly transmissible illness. For this narrative review, we used PubMed, Google Scholar, and Scopus to obtain epidemiological data, pre-clinical and clinical trial outcomes, and recent therapeutic alternatives for treating COVID-19 viral infection. In this study, we discussed the disease's origin, etiology, transmission, current advances in clinical diagnostic technologies, different new therapeutic targets, pathophysiology, and future therapy options for this devastating virus. Finally, this review delves further into the hype surrounding the SARS-CoV-2 illness, as well as present and potential COVID-19 therapies.
Keywords: Viral infection